New perspectives on satisfaction and loyalty in festival tourism: The function of tangible and intangible attributes - Molina-Gómez, Jesús; Mercade-Mele, Pere; Almeida-García, Fernando; Ruiz-Berrón, Raquel (Plos One, 2021)
This research explains how attributes perceived during the festival celebration generate loyalty in terms of satisfaction. As regard, tangible aspects (festival entertainment and aesthetics) and intangible aspects (escapism and education) shall be differentiated. A theoretical model is proposed, which explains the effects of festival attributes on satisfaction and loyalty through structural equation modelling. The model was estimated with a sample of 440 people attending Weekend Beach Festival in Spain. The research proves the relationship between attributes and loyalty through satisfaction as a moderating variable; likewise, tangible attributes are deemed to have a greater influence on loyalty, specifically, the aesthetic/environment experience.
Keywords: Festivales - Marketing; Festival Tourism; Intangible Attributes; Tangible Attributes; Satisfaction; Loyalty